The Quantum Exodus : Jewish Fugitives, The Atomic Bomb, and the Holocaust - Fraser, Gordon (New York Oxford University Press, 2016)
"It was no accident that the Holocaust and the Atomic Bomb happened at the same time. When the Nazis came into power in 1933, their initial objective was not to get rid of Jews. Rather, their aim was to refine German culture: Jewish professors and teachers at fine universities were sacked. Atomic science had attracted a lot of Jewish talent, and as Albert Einstein and other quantum exiles scattered, they realized that they held the key to a weapon of unimaginable power. Convinced that their gentile counterparts in Germany had come to the same conclusion, and having witnessed what the Nazis were prepared to do, the exiles were afraid. They had to get to the Atomic Bomb first. The Nazis meanwhile had acquired a more pressing objective: their persecution of the Jews had evolved into extermination. Two dreadful projects--the Bomb and the Holocaust--became locked a grisly race."--Jacket.
Include Illustrations and Index
Keywords: Influence (Literary, artistic, etc.) -- Jewish scientists -- Buddhism and politics